Average Density Model (JIM) In Expressive Performance Among Second-Grade Students (Journal of the College of Basic Education, 2026)
The researcher aimed to identify the effect of the (JIM) model on the expressive performance of second-year intermediate students in the subject of expression. To achieve this objective, the researcher formulated the following null hypothesis: There is no statistically significant difference at the significance level of (0.05) between the mean scores of the experimental group students studying expression using the JIM model and the mean scores of the control group students studying the same subject using the traditional method in the series of tests prepared by the researcher. The researcher adopted a quasi-experimental design for the two research groups. Both the experimental and control groups were subjected to the series of tests. The researcher selected intermediate and secondary schools affiliated with the General Directorate of Education in Diyala Governorate to form the research population. The research sample consisted of 70 students: (35) for the experimental group and (35) for the control group. The control group, and after conducting his research, the researcher reached results, the most important of which was the superiority of the experimental group students over the control group students in expressive performance.